Prevalence, incidence and management of atopic dermatitis in Australian general practice using routinely collected data from MedicineInsight. (15th March 2020) - Chidwick, Kendal; Busingye, Doreen; Pollack, Allan; Osman, Rawa; Yoo, Jeannie; Blogg, Suzanne; Rubel, Diana; Smith, Saxon
Abstract: Background/Objectives: The prevalence of atopic dermatitis (AD) has increased significantly in industrialised countries in recent decades but data about the incidence or prevalence of AD in Australia are sparse. We aimed to determine the prevalence and incidence of AD among patients seen in Australian general practice and the use of specified medicines. Methods: This was a cross‐sectional study of 2.1 million patients attending 494 general practices in the MedicineInsight program from 1 January 2017 to 31 December 2018. We assessed the prevalence (lifetime and current), incidence, management and severity of AD. Results: The lifetime (ever diagnosed) prevalence of AD in this general practice population was 16.4% and was greater in females (17.3%) than males (15.3%). One in five patients with AD were classified as having moderate‐to‐severe disease. Prevalence over the last two years was 6.3%. The incidence of AD in 2018 was 2.0% and was greater in females (2.2%) and for patients aged 0–4 years (3.9%). Patients with AD had an increased risk of insomnia, anxiety and depression, compared to those with no recorded AD. For AD patients, topical corticosteroids were the most commonly prescribed AD medication (36.5%) and topical calcineurin inhibitors the least (0.1%), with systemic corticosteroids (15.6%) more commonly prescribed than other immunosuppressants (0.9%). Conclusions: Our findings provide important insights into the epidemiology of AD and its management in Australian general practice. This information is likely to be useful in planning effective interventions to support GPs in the optimal management of patients with AD.